Pembelajaran dengan Memanfaatkan Media Sampah untuk Meningkatkan Kemampuan Literasi dan Keterampilan Berpikir Kreatif Siswa Sekolah Dasar - Pudji Astutik, Pipit (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objectives are to improve literacy ability and creative thinking in learning through garbage media. Prior observation indicated that the fifth-grade children’s literacy and creative thinking in learning were presumably low. Literacy and creative thinking skills can be improved by the implementation of learning bases environment. Children’s literacy and creative thinking could be improved through learning integrated with learning sources taken from their environment. Learning sources taken from the environment may consist of anything natural including garbage. A classroom action research was conducted with its four phases, namely: planning, action, observation, and reflection. Data on children’s literacy was collected after action. Whereas their creative thinking was observed throughout learning. Research results show that children’s mean score on literacy = 68.00 with sufficient category in cycle 1 was improved to = 78.00 with good category in cycle 2. Their creative thinking skill was improved to = 71.00 with sufficient category in cycle 1; and their creative thinking skill was improved to 80.00 in cycle 2 with good category.